Design and implementation ofserver security alarm system in campus network - Bin PANG; Hua LI; You-yi WANG; Shuai YAN; Zhi-he YANG (Tongxin xuebao)
A safety test using open source tools was put forward to construct four layer network scan architecture pattern for monitoring server safety,it also can get an automatic analysis report of threaten for the administrators.Through the timing detection mechanism based on process from hardware to software,from the operating system to the service application even to the dynamic page script to build a full range,customizable，flexible combination of multi-level security